Safe pseudoelastic limit range under torsional loading with Reciproc Blue. (16th August 2018) - Ha, J.‐H.; De‐Deus, G.; Versluis, A.; Kwak, S. W.; Kim, H.‐C.
Abstract: Aim: To determine the distortional angle and torsional load at the pseudoelastic limit of Reciproc Blue instruments and to verify the safety of using pre‐set dedicated motors designed for use with the original Reciproc instruments. Methodology: Two torsional conditions of Reciproc R25 and Reciproc Blue R25 were tested using a custom device. The first condition fixed the file tips at 3 mm and repetitively rotated them, with gradually increasing angles, from 10° to 270°, and the resulting torque was recorded ( n  =   15). The second test involved a single continuous rotation until fracture ( n  =   15). The pseudoelastic limits of the instruments were determined from their torque‐rotation curves. For statistical analysis, two‐way analysis of variance and t ‐tests were used, at a 95% significance level. Tested specimens were examined using field‐emission scanning electron microscopy (FE‐SEM). Results: The angle at the pseudoelastic limit was significantly greater for Reciproc Blue than Reciproc, regardless of test mode ( P  < 0.05). When torsional loading was repeated, using gradually increasing rotational angles, the torsional resistance was significantly lower than for a single rotation ( P  < 0.05). However, under all test conditions, the pseudoelastic limit was below the pre‐set 170° of the dedicated reciprocating motor. FE‐SEM evaluation of the lateral aspects of the instruments revealed numerous longitudinal microcracks running along their long axis. For Reciproc Blue groups, the file shaft machining grooves were distorted after repetitive and continuous torsional tests. Conclusions: The 170° pre‐set angle of the dedicated endodontic motors for the Reciproc system was safe for Reciproc Blue in single or time‐restricted use.